Elaboração e análise de indicadores sociais para o apoio à tomada de decisão no processo de despoluição da Baía de Guanabara - Guimarães, Vanessa Gonçalves. (2017)
Guanabara Bay's basin show profound contrasts, where in the heart of the second biggest metropolis in the country, there still are population contingents without access to basic sanitation facilities. Despite the efforts invested in depollution since the 90s, there isn’t a perception, by the public opinion, that there has been an evolution in its deteriorated social situation. The importance of social indicators rise in a moment when it is necessary to account for the public investments and results obtained, direct actions towards social matters and places in urgent situations and keep track of the results so that possible adjustments of actions can be made in order to obtain better results. Today's discussion agenda formed the basis for the elaboration of a system of social indicators. Three basins that are in process of depollution have also been studied, with a focus in their approaches to social matters. A theoric model of indicators was elaborated and tested in a fragment of the Guanabara Bay’s basin, with the use of public available data. The model proved to be a useful tool in a holistic approach of the basin since it informs about the best directioning of depollution actions to produce more effective results on both social and environmental issues.